Further mathematics for Science and engineering / Nor Hanim Abd Rahman... [et al.] - Abd Rahman, Nor Hanim; Mohd Abd Rahman, Shakirah; Kechil, Rafizah; Cheng, Siak Peng; Hamed, Salina (Unit Penulisan Dan Penerbitan JSKM, 2015)
Definition: A set of real or complex numbers arranged in a rectangular array having m rows and n columns. This set is called a matrix of order m x n (read as m by n). The number aij is called an element in row i and column j. The capital letters are used to denote matrices and the corresponding lower case letters are used to denote the elements.